2006
DOI: 10.1083/jcb.200511126
|View full text |Cite
|
Sign up to set email alerts
|

The selective continued linkage of centromeres from mitosis to interphase in the absence of mammalian separase

Abstract: Separase is an evolutionarily conserved protease that is essential for chromosome segregation and cleaves cohesin Scc1/Rad21, which joins the sister chromatids together. Although mammalian separase also functions in chromosome segregation, our understanding of this process in mammals is still incomplete. We generated separase knockout mice, reporting an essential function for mammalian separase. Separase-deficient mouse embryonic fibroblasts exhibited severely restrained increases in cell number, polyploid chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
69
1
8

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 25 publications
3
69
1
8
Order By: Relevance
“…36,37 Securin degradation frees separase which has been proposed to cleave the remaining cohesin at the centromeres, 38,39 permitting sister chromatid separation during anaphase. 40,41 However, recent reports have shown that the APC/C and its activator Cdc20 are dispensable for sister centromere separation. [42][43][44][45][46] These data indicated that although the APC/C plays an important role in the fidelity of anaphase, the regulation of sister chromatid separation is more complex in mammals than was previously thought (reviewed in ref.…”
Section: Introductionmentioning
confidence: 99%
“…36,37 Securin degradation frees separase which has been proposed to cleave the remaining cohesin at the centromeres, 38,39 permitting sister chromatid separation during anaphase. 40,41 However, recent reports have shown that the APC/C and its activator Cdc20 are dispensable for sister centromere separation. [42][43][44][45][46] These data indicated that although the APC/C plays an important role in the fidelity of anaphase, the regulation of sister chromatid separation is more complex in mammals than was previously thought (reviewed in ref.…”
Section: Introductionmentioning
confidence: 99%
“…Dysregulation of the mitotic machinery that helps maintain chromosomal stability in mammary cells can result in aneuploidy and subsequently, cancer formation. We focused on Separase for the following reasons that have important implications for breast cancer: (i) Separase plays a central role in promoting faithful chromosome segregation; (ii) our previous studies strongly indicated that hormonal stimulation of p53-null mice mammary gland results in overexpression of the ESPL1 and Separase protein, which may be a direct cause of aneuploidy (5); and (iii) siRNA-mediated knockdown of Separase and Separase deficient mouse embryonic fibroblasts results in genomic instability (6)(7)(8).…”
mentioning
confidence: 99%
“…66 In addition to revealing the preference of AML1-ETO for duplicated AML1 sites, we also reported separase as a novel AML1-ETO target gene and used it as a model to demonstrate the regulation of AML1-ETO by multiple sites. Separase is essential for proper chromosome segregation, 67,68 and an inactivating mutation causes genomic instability and increased frequency of epithelial cancer in a zebrafish model. 69 Since separase expression is modulated in AML1-ETO-expressing U937T cells, t(8;21) patients might have deregulated separase expression that may contribute to the deregulation of the cell cycle and the associated gain and loss of chromosomes observed in these patients.…”
mentioning
confidence: 99%